Parent - Child Interaction in Relation to Creative Thinking Ability of Secondary School Students - Siddiqi, Saima (American Journal of Education and Learning, 2019)
The present study was conducted with two major objectives, i.e. to discover the difference, if any, in the parent child interaction with regard to location and gender variation; and to find out the relationship between parent-child interaction and creativity. The sample of the study consisted of 100 higher secondary school students of Aligarh district comprising of 50 girls and 50 boys belonging to both rural and urban area. The data was collected using two scales including verbal and Non-verbal test of creativity developed and standardized by Dr. Baquer Mehdi and Parent-Child Interaction Scale developed and standardized by S.V.Kale. The result of the study showed that Creative thinking and parent-child interaction puts differential impact on both girls and boys; urban and rural area, whereas creative thinking does not differentiate between boys and girls, the students were found to be fairly competent in verbal, non-verbal, originality and elaboration aspects of creativity, and both parent-child interaction and creative thinking ability were significantly related to each other.